The Antimicrobial Properties of The Major Compounds Found in South African Propolis - Kharsany, Khadija (My University, 2019)
Propolis is a resinous substance produced by the Apis mellifera bee. The compounds predominantly found in South African propolis are the flavonoids pinocembrin, galangin, and chrysin. The aim of this study was to obtain an understanding of the antimicrobial activity of these compounds, both singularly and in combination, and to investigate the role of interactions between the compounds. To observe the effects of the compounds against planktonic micro-organisms, the minimum inhibitory concentrations (MIC) and minimum bactericidal concentrations (MBC) assays were undertaken. Combinations were tested at equal ratios using the MIC assay, the results of which were interpreted using the fractional inhibitory concentration (FIC) index. Varied ratio combinations using the MIC method were also undertaken and presented in isobolograms. Results from six bacterial strains and three yeast strains demonstrated that the singular compounds displayed moderate to weak activity, and that the activity of pinocembrin, galangin, and chrysin was improved when used in combination. When tested at 1:1 ratio, synergy occurred in six out of the 27 combinations (22%) whilst nine combinations (30%) were additive, and the remaining 12 combinations (44%) were non-interactive. No combination showed antagonism. The 1:1 combination of galangin and chrysin appeared to be the most effective, as it was synergistic against three of the nine micro-organisms (33%) tested, and additive against another three. Pinocembrin, galangin, and chrysin were then tested at varying ratio combinations against three micro-organisms, which produced nine isobolograms and a total of 81 ratios. From these 81 ratios, 32 ratios (40%) showed synergy, while 31 ratios (38%) were additive and the remaining 18 ratios (22%) were non-interactive. The combination of galangin and chrysin against C. tropicalis displayed the best activity, as all nine ratios of these two compounds in combination, showed synergy. The triple combination which used pinocembrin, galangin, and chrysin at a 1:1:1 ratio against nine pathogens, produced synergy against six of the nine micro-organisms (67%) tested and additivity against the remaining three (33%) micro-organisms. Selected combinations 4 possessed bactericidal activity, although the compounds on their own demonstrated no bactericidal activity at the concentrations tested. The most pronounced bactericidal activity was observed from the combination of galangin with chrysin against Candida tropicalis, with an MBC value of 0.16 mg/ml. Anti-quorum sensing (QS) testing was undertaken using Chromobacterium violaceum as a monitor strain. The broth macrodilution method was used. In addition, an anti-QS broth microdilution method was tested for the first time in this study. Results from the broth macrodilution method showed that pinocembrin, galangin and chrysin, and their combinations, were capable of inhibiting violacein production from C. violaceum. When tested singularly, pinocembrin, galangin and chrysin all showed minimum quorum sensing inhibitory concentration (MQSIC) values of 0.31 mg/ml or less, and MBC values of 2.5 mg/ml or less. When tested together, the combinations of pinocembrin, galangin and chrysin showed MQSIC values of 0.16 mg/ml or less, and MBC values of 1.25 mg/ml or less. The combination of pinocembrin and galangin was the most promising, with a MQSIC value of 0.08 mg/ml and an MBC values of 0.31 mg/ml. Three out of four combinations (75%) demonstrated synergy through inhibiting QS, while the combination of pinocembrin and chrysin was additive. Results from the broth microdilution method corresponded with those of the macrodilution method qualitatively, although the quantitative results differed. To assess the effects of pinocembrin, galangin and chrysin on biofilm prevention and disruption, the crystal violet (CV) assay was used. No clear pattern on antibiofilm activity was observed, although selected compounds and combinations were shown to be effective in inhibiting biofilms. Good biofilm inhibitory activity was noted for 18 out of 45 (40%) of the studies when the compounds were tested independently against the three micro-organisms at various timeframes. The best activity from a single compound was observed for chrysin against Escherichia coli at 24 hr (79.73% inhibition). When the compounds were tested in combination at a 1:1 ratio, only nine out of 60 (15%) combinations tested showed good inhibitory activity. However, the triple combination showed the best inhibitory activity of 100% when tested against E. coli at 24 hrs. The toxicity of pinocembrin, galangin and chrysin was screened using the brine shrimp lethality assay (BSLA) after an exposure period of 24 hr. None of the compounds or combinations displayed 5 toxicity. When tested independently, the highest percentage mortality was noted from galangin, at 23.53%. When the compounds were tested in combination, the highest percentage mortality was observed for the combination of galangin and chrysin, at 6.17%. Three of the four combinations showed reduced toxicity. This study has clearly demonstrated that the combination of the compounds pinocembrin, galangin and chrysin found in South African propolis synergistically enhances the antimicrobial activity of South African propolis on a number of levels whilst simultaneously further reducing the toxicity of the compounds. Furthermore, this study provides a convincing example of the need to examine compound interactions and to not always follow the reductionist approach of searching for a single active compound in natural product research.
A dissertation submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Master of Pharmacy June 2019
Keywords: Beeswax; Propolis